Perception of Periodontal Diseases among Antenatal Care Providers (Medical Forum Monthly, 2021)
Objective: To assess the awareness, knowledge and attitude of antenatal care providers (ANC) regarding the periodontal disease and its association with adverse pregnancy outcomes in tertiary care hospitals of Pakistan.Study Design: A cross sectional studyPlace and Duration of Study: This study was conducted at the Four Tertiary Care Hospitals of Islamabad and Rawalpindi among Antenatal Health Care (ANC) providers from December 2019 to March 2020.Materials and Methods: Approval was sort from the ethical review committee of Armed Forces Institute of Dentistry Rawalpindi. A predesigned questionnaire, containing the demographic information to judge the knowledge, attitude, and awareness among 114 ANC providers over the period of four months regarding the association of periodontal disease and adverse pregnancy outcomes.Results: Overall response rate was 93%. Most of participants (92%) had the knowledge that bleeding from gums was the first sign of inflammatory process, but 59% did not know about the adverse effects of periodontal disease on pregnancy. About 62% of experienced practitioners knew that 2nd trimester is safe for dental treatment but 75% of them never inquired about oral health of expecting women.Conclusion: The study concludes that knowledge of Health care providers about periodontal disease in pregnant females is lacking and their clinical behavior regarding oral and periodontal health was also not adequate. Therefore, inter-professional education programs should be implemented as a part of continuing medical education to bridge the knowledge gap between periodontist and ANC providers.